C/EBPα Activates Pre-existing and De Novo Macrophage Enhancers during Induced Pre-B Cell Transdifferentiation and Myelopoiesis - van Oevelen, Chris; Collombet, Samuel; Vicent, Guillermo; Hoogenkamp, Maarten; Lepoivre, Cyrille; Badeaux, Aimee; Bussmann, Lars; Sardina, Jose Luis; Thieffry, Denis; Beato, Miguel; Shi, Yang; Bonifer, Constanze; et al. (Stem cell reports, 2015)
Transcription-factor-induced somatic cell conversions are highly relevant for both basic and clinical research yet their mechanism is not fully understood and it is unclear whether they reflect normal differentiation processes. Here we show that during pre-B-cell-to-macrophage transdifferentiation, C/EBPα binds to two types of myeloid enhancers in B cells: pre-existing enhancers that are bound by PU.1, providing a platform for incoming C/EBPα; and de novo enhancers that are targeted by C/EBPα, acting as a pioneer factor for subsequent binding by PU.1. The order of factor binding dictates the upregulation kinetics of nearby genes. Pre-existing enhancers are broadly active throughout the hematopoietic lineage tree, including B cells. In contrast, de novo enhancers are silent in most cell types except in myeloid cells where they become activated by C/EBP factors. Our data suggest that C/EBPα recapitulates physiological developmental processes by short-circuiting two macrophage enhancer pathways in pre-B cells. [Display omitted] •C/EBPα activates two classes of prospective myeloid enhancers in B cells•Pre-existing enhancers are bound by PU.1 and become hyper-activated by C/EBPα•C/EBPα acts as a pioneer factor with delayed kinetics on de novo enhancers•The two types of enhancers direct myeloid cell fate in B cells and hematopoiesis In this study, Graf and colleagues show that, during B-cell-to-macrophage transdifferentiation, C/EBPα activates two types of myeloid enhancers in B cells. The two enhancer types are differentially activated, dictating gene expression levels of macrophage genes during the conversion of B cells into macrophages and normal hematopoiesis.